The Determinants Affecting the Violent Crime in Indonesia and Thailand (1990–2019) - Erwin Kurniawan A.; Adi Wijaya; Andriawan Kustiawan (Облік і фінанси, 2023)
Due to the global increase in crime, many countries and regions have ceased to be safe places to live. The growth of global crime figures leads to the deterioration of humankind’s quality of life. This study aims to examine the causality of the total violent crime determinants in Indonesia and Thailand from 1990 to 2019. The data were collected from the Global Economy and the Nasdaq Database. The variables used in this study are the total violent crime, Gross National Income per capita (GNIpc), unemployment rate, social security expenditure, and value of alcoholic beverage consumption. All the variables were converted into a logarithmic form. Both Indonesia and Thailand’s total violent crimes contain these wrongdoings: murder, rape, robbery (with firearms and without firearms), which includes gang robbery, and causing bodily injuries. This research has two models as both analyze different countries: Indonesia and Thailand. The empirical tests have proven the variables affecting the model of Indonesia and Thailand in the long run and short run based on the data from 1990–2019. In the long run, total violent crime, the unemployment rate, and alcoholic beverage consumption will affect the model of Indonesia by bringing equilibrium whenever disequilibrium happens. In the short run, the GNIpc has a unidirectional relationship with the Unemployment rate. In Thailand, alcoholic beverage consumption is the only reliant variable which will be self-perpetuated and affect the model in the long run. In the short run, alcoholic beverage consumption will be affected by the Unemployment rate and GNIpc of Thailand. In addition, instead of total violent crime being the dependent variable, it could affect Thailand’s social security expenditures in the short run. This study provided a clearer view of the violent crime determinants in Indonesia and Thailand. Moreover, these empirical findings could help in policy-making to curb the worsening social violence in both countries.